Cover Image, Volume 37, Issue 2. Issue 2 (17th December 2015) - Unknown
Abstract : Saturn systems are nanohoops bound to fullerenes through noncovalent interactions. On page 194 (DOI:10.1002/jcc.23979 ), Habib Rehman, Nida A. McKee, and Michael L. McKee examine several systems using density functional methods. If the size is compatible, the nanohoop binds around the meridian of C60 with a significant free energy of binding. C60 @(T‐C2 H2 )8 is an example of such a system where T‐(C2 H2 )8 is a nanohoop of eight thiophenes linked by eight ethene units. The calculated free energy of binding in toluene at 298 K is ‐5.4 kcal/mol which indicates that, if the ring system can be synthesized, the C60 @(T‐C2 H2 )8 complex should be observable.